The growth of thin Cu layers on Ni(111) studied by CO titration and photoelectron spectroscopy - Koschel, Herbert; Held, Georg; Steinrück, Hans-Peter (Surface Science, 2000)
The growth of thin Cu layers (up to 14 ML) on Ni(111) was studied by temperature-programmed desorption (TPD) of CO and X-ray photoelectron spectroscopy (XPS). CO TPD spectra display desorption features from both nickel- and copper-terminated areas, which are clearly separated in temperature. Using XPS and TPD for titrating the uncovered Ni areas, the quality of the copper layer in the 1 ML range was studied as a function of annealing temperature. We find that a pseudomorphic Cu monolayer on Ni(111) is best produced by evaporating the appropriate amount of Cu onto the cold sample at 100 K, followed by annealing to temperatures around 800 K. This temperature is high enough to convert three-dimensional islands that are found at low temperatures into smooth two-dimensional Cu layers, but low enough to avoid alloying, which is observed for higher annealing temperatures. For higher Cu coverages, annealing to 800 K leads to significant diffusion of Ni atoms into the Cu multilayer. © 2000 Elsevier Science B.V. All rights reserved.